Effect of alkaline pre-treatment on physical, optical and mechanical properties of semi-chemical NSSC wheat straw pulp - Soodeh Zhand (Regional Information Center for Science and Technology (RICeST), 2013)
In this study the effect of alkaline pretreatment with 1% NaOH on physical, optical and mechanical properties and refining of NSSC (Neutral Sulfite Semi Chemical) wheat straw pulp were investigated. The wheat straw (Zagros Sp.) was obtained from croplands Golestan province. Splinted wheat straw was pretreated with 1% NaOH(on the basis of OD weight) at 70 degrees for 30 minutes. The main pulping was performed at 160 ˚C with the fixed ratio of 5:1 Na2S03 and NaOH. After pulping defibration was done by lab-refiner to 380±25ml (CSF) and total yield and changes in Kappa was determined. Hand sheets of 60 gr. /m² were made on the basis of TAPPI standard and physical, optical and mechanical properties determined.  The results show that alkaline pre-treatment has a significant effect in increasing of physical, optical and mechanical properties. Calculating primary freeness of pulps indicates that by increasing chemical compounds and NaOH, freeness decreases and that by increasing chemical compounds paper density increases, whereas yield, caliper and bulk decrease.